New and rare lichens of the family Megasporaceae discovered in Poland - Szczepańska, Katarzyna; Kukwa, Martin; Guzow-Krzemińska, Beata; Urbaniak, Jacek (Phytotaxa, 2023)
Based on a revision of historic herbarium material and recently collected specimens, six lichenized fungi of the family Megasporaceae have been identified. Four of them, Aspicilia verrucigera, Oxneriaria supertegens, Sagedia mastrucata and S. zonata are reported for the first time from Poland. Also, we present new localities for two species, Aspicilia goettweigensis and A. polychroma, that have been rarely reported in the country. The characteristics of all these species, as well as their ecology and geographical distribution, are presented and briefly discussed. In addition, nucITS rDNA and mtSSU rDNA were sequenced for some specimens to confirm their identifications.